Disillusionment and Death in Ourika and “La Noire de...” - Rangarajan, Sudarsan (Dalhousie French Studies, 2022)
This study proposes to compare Claire de Duras’s Ourika (1824) and Ousmane Sembène’s “La Noire de...” (1962). The two novellas concern the assimilation of a Senegalese woman in the French society. Ourika is a young woman raised and educated in an aristocratic environment, while Diouana, the protagonist of Sembène’s story, who works as a maid, is illiterate. But the difference between the two women disappears as racism emerges. Using Fanon and Bhabha, this study focuses on the following aspects: Commodification and the loss of self; stigmatization and the protagonist as the Other; alienation and death; and suppressed voices and posthumous narratives. The essay concludes with a discussion of the significance of the struggles of the two protagonists, by extension, for Francophone African writers in the postcolonial context.